1992
DOI: 10.1007/bf00968013
|View full text |Cite
|
Sign up to set email alerts
|

N-type calcium channels are involved in the dopamine releasing effect of nicotine

Abstract: Mouse striatum was incubated with [3H]dopamine ([3H]DA) and superfused with and the tritium efflux induced by nicotine, electrical stimulation, or simultaneous nicotine and electrical stimulation was measured, to characterize the role of different Ca2+ channels in the transmitter release. Nicotine stimulation and electrical stimulation exerted additive effects on tritium efflux. Separation of the released radioactivity on alumina columns indicated that nicotine or electrical stimulation increases the release o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 25 publications
1
8
1
1
Order By: Relevance
“…Because there exists a general consensus that mesolimbic dopaminergic transmission underlies nicotine-induced locomotion, dopamine is the likely neurotransmitter candidate (Clarke et al 1988). However, our findings appear to be in some conflict with those recently reported by Harsing et al (1992). They concluded that nicotine-induced dopamine release in the striatum is mediated by the N-type calcium channel.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Because there exists a general consensus that mesolimbic dopaminergic transmission underlies nicotine-induced locomotion, dopamine is the likely neurotransmitter candidate (Clarke et al 1988). However, our findings appear to be in some conflict with those recently reported by Harsing et al (1992). They concluded that nicotine-induced dopamine release in the striatum is mediated by the N-type calcium channel.…”
Section: Discussioncontrasting
confidence: 83%
“…There is evidence that suggests both the L-and N-type calcium channels play a role in the release of dopamine induced by drugs of abuse (Pani et al 1990;Harsing et al 1992). Pani et al (1990) found that cocaine-induced dopamine release is blocked by L-type calcium channel blockers, whereas Harsing et al (1992) reported that dopamine release by nicotine is attenuated by omega-conotoxin, an N-type calcium channel antagonist.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Clinical relevance of slowed deactivation. Ca V 2 channels are localized within nerve terminals in both the central and peripheral nervous systems and serve as the major pathway for Ca 2ϩ entry that triggers neurotransmitter release (Harsing et al 1992;Hirning et al 1988;Shimosawa et al 2004;Wheeler et al 1994). Until the identification of R-roscovitine, there were no drugs available to enhance Ca 2ϩ influx through presynaptic Ca V 2 channels (Buraei et al 2005(Buraei et al , 2007Yan et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the enhanced free intracellular Ca 2þ , an exocytotic process may trigger dopamine release from vesicular pool. In many experimental conditions, dopamine release evoked by nicotine has been reported to be partly external Ca 2þ -dependent (Harsing et al, 1992).…”
Section: Dopamine Release Evoked By Ion Channel-coupled Receptorsmentioning
confidence: 99%